2014
DOI: 10.5539/ijef.v6n4p240
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of the Dividend Policy: An Empirical Study on the Lebanese Listed Banks

Abstract: This research aims at investigating the factors determining the dividend payout policy in the Lebanese banks listed on the Beirut Stock Exchange. This study considers the impact of seven variables, namely, profitability, liquidity, leverage, firm size, growth, firm risk and previous year's dividend payout on the dividend payout ratios by using an unbalanced panel dataset of listed banks between the years of 2005 and 2011. Two models were tested using the OLS and the dynamic panel regressions. Empirical results… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
51
0
26

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(88 citation statements)
references
References 54 publications
11
51
0
26
Order By: Relevance
“…However, the firm's likelihood to pay dividends is affected negatively by firm's financial leverage at 0.01 level of significance, an indication that companies suffer from high debt are less likely to pay dividends to their shareholders. These results are consistent with (Dickens et al, 2002;Ho, 2003;Aivazian et al, 2003;Maladjian & El Khoury, 2014;Kuzucu, 2015;Yusof & Ismail 2016) …”
Section: Constantsupporting
confidence: 82%
See 1 more Smart Citation
“…However, the firm's likelihood to pay dividends is affected negatively by firm's financial leverage at 0.01 level of significance, an indication that companies suffer from high debt are less likely to pay dividends to their shareholders. These results are consistent with (Dickens et al, 2002;Ho, 2003;Aivazian et al, 2003;Maladjian & El Khoury, 2014;Kuzucu, 2015;Yusof & Ismail 2016) …”
Section: Constantsupporting
confidence: 82%
“…Kuzucu (2015) argued that large companies tend to pay higher amount of dividends to decrease agency costs. Whereas, (Dickens et al, 2002;Maladjian& El Khoury, 2014) argued that large companies pay higher amount of dividends since these companies tend to be more competitive and attract investors. Financial leverage is also included as a control variable which measured as the ratio of total debt to total assets.…”
Section: Control Variablesmentioning
confidence: 99%
“…Such as if there is increase in profitability of a firm it would be assumed and proved to increase dividend payout ratio of any corporation (Mehta,2012, Nuhu, 2014,Gill, Biger, & Tibrewala 2010,Zameer et al 2013 but this relationship is being rejected by Jozwiak (2014) Maladjian & Khoury (2014) explored the impact of profitability, growth, liquidity and size of firm, leverage, risk, and previous year's dividends on dividend policy of Lebanese banks registered on Beirut Stock Exchange. They concluded that out of seven variables studied, five variables are statistically significant whereas profitability and liquidity are statistically insignificant.…”
Section: Research Problem and Knowledge Gapmentioning
confidence: 99%
“…In contrary, numerous researchers believe that perfect capital market does not exist and various real world factors influence company's dividend payout policy (Mehta, 2012, Nuhu, 2014, Maladjian & Khoury, 2014, Rafique, 2012, Gill, Biger & Tibrewala, 2010.…”
Section: Introductionmentioning
confidence: 99%
“…First, the findings of existing studies relating to the determinants of dividend policy are largely mixed (Osobov & Denis, 2008;Banga & Gupta, 2010;Nnadi et al, 2013;Maldajian & El Khoury, 2014;Brunzell et al, 2014). Second, existing studies have investigated largely how general firm level characteristics, such as cash flow (Travlos et al, 2001;Fama & French, 2001), firm size (Al-Malkawi, 2007;Al-Kuwari, 2009Jiraporn et al, 2011), leverage (Al-Shubiri, 2011;Afza & Mirza, 2011;Rafique, 2012;Emamalizadeh et al, 2013) and return on assets (Amidu, 2007;Gill et al, 2010;Adil et al, 2011;Ouma, 2012) affect dividend pay-out.…”
Section: Introductionmentioning
confidence: 99%